2019
DOI: 10.1038/s41598-019-54679-w
|View full text |Cite
|
Sign up to set email alerts
|

Agastache honey has superior antifungal activity in comparison with important commercial honeys

Abstract: There is an urgent need for new effective antifungal agents suitable for the treatment of superficial skin infections, since acquired resistance of fungi to currently available agents is increasing. The antifungal activity of mono-floral Agastache honey and commercially available honeys were tested against dermatophytes (T. mentagrophytes and T. rubrum) and C. albicans (ATCC 10231 and a clinical isolate) by agar well diffusion and micro-dilution (AWD and MD). In AWD and MD assays, Agastache honey was effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 67 publications
1
27
2
1
Order By: Relevance
“…The dermatophytes appeared substantially more susceptible to jarrah honey than has been reported for other H 2 O 2 -producing honeys, where MICs have ranged from 5–39% ( v / v ) [ 19 , 20 ]. Our results are in contrast to a recent study of a commercial jarrah honey, however, which had no activity against Trichophyton mentagrophytes and T. rubrum [ 28 ]. H 2 O 2 -producing honeys can be highly variable in activity, which can be influenced by age, processing and storage conditions as well as bee health and geographic factors, and even fresh and unprocessed samples can range from very high to negligible activity [ 21 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The dermatophytes appeared substantially more susceptible to jarrah honey than has been reported for other H 2 O 2 -producing honeys, where MICs have ranged from 5–39% ( v / v ) [ 19 , 20 ]. Our results are in contrast to a recent study of a commercial jarrah honey, however, which had no activity against Trichophyton mentagrophytes and T. rubrum [ 28 ]. H 2 O 2 -producing honeys can be highly variable in activity, which can be influenced by age, processing and storage conditions as well as bee health and geographic factors, and even fresh and unprocessed samples can range from very high to negligible activity [ 21 , 29 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Increasing the concentration of honey from 16% to 40% led to a 2-log reduction in the CFU of C. auris , while the CFUs of the other Candida species were also reduced by 1- to 4-log, with C. glabrata being least susceptible and C. krusei most susceptible. As previous studies found differences in the susceptibility of yeasts to different types of honey [ 11 , 12 , 13 ], the five Candida species were also treated with a local unprocessed honey. Local unprocessed honey (40%) caused a 2- to 5-log reduction in all Candida species.…”
Section: Discussionmentioning
confidence: 99%
“…A promising candidate for the treatment of yeasts in wounds and skin colonization is honey. Medical-grade honey follows strict criteria to guarantee its safety, quality, and efficacy, and was also found to be effective in inhibiting different Candida species, such as C. albicans and C. tropicalis [ 10 , 11 , 12 , 13 ]. Medical-grade honey consists of more than 200 different components influenced by its botanical origin, geographical location and secretions from the bee [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Honey is definitely the most studied bee product regarding its antimicrobial properties. It is reported to exert antibacterial [ 4 , 5 , 6 , 7 ], antifungal [ 8 ], and antiviral activity [ 9 , 10 , 11 ]. In addition, it exhibits anti-inflammatory and wound-healing action [ 12 ], as well as anticancer properties [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%